Shaping Smart AI-titude among Secondary ESL Students in Nigeria: An Exploratory Study - Amuseghan, Sunday Adejimola; Emmanuel, Isaac Friday (Universitas Kapuas, 2025)
As access to Artificial Intelligence (AI) grows in Nigeria, tutorial videos explaining how AI tools can be exploited to excel in examinations began to emerge online. However, there is a concern that secondary school students may come to perceive it as a shortcut to bypass learning, thereby leading to negative attitudes toward responsible AI use. This study investigated the cognitive awareness, affective dispositions, and behavioural practices of secondary school students in Ondo State regarding AI, while also proposing strategies for cultivating constructive “Smart AI-titudes.” A descriptive survey design was employed which involved 350 students selected through simple random sampling technique in Ondo state. A structured questionnaire titled: Smart AI-titude Questionnaire (SAQ) (r=0.81) was used for data collection. Data collected were analyzed using descriptive statistics and PPMC. Findings revealed that students demonstrated very high awareness of what AI means (????̄ = 3.03) and its tools such as ChatGPT, Perplexity, and Gemini (????̄ = 2.90). More so, students strongly agreed that they trust AI information (????̄ = 3.21), and feel comfortable using tools like ChatGPT (????̄ = 3.23). However, they disagreed with using AI to understand difficult topics (????̄ = 1.38), yet strongly agreed to using it for assignments with little effort (????̄ = 3.70). The study concludes that students’ recognition-level awareness does not match with constructive practices. Thi study, among others, recommends that AI literacy should be integrated into the curriculum and equips teachers to model responsible AI use.